ECloud - Magnetotelluric Webapp. Issue 1 (1st December 2018) - Pethick, Andrew; Harris, Brett; Lebedev, Petr
Abstract : Geophysical web applications are highly underrated. There are many potential benefits for transitioning to a cloud based web applications including compatibility improvement, low on-going operating costs and better access to existing third-party code and tools for facilitating rapid development. For users, time spent on installation, general IT maintenance such license management and upgrading is minimized. While web applications for business style applications are deeply established, scientific applications on the web are only just emerging. This research builds upon our previous feasibility study (Pethick and Harris 2015), which was the development of a 1D MT web application. This is to be redevelop into a commercial grade cloud hosted geophysical inversion web app that can cooperatively invert seismic and magnetotelluric (MT) data. Our software, ECloud, is designed to be user friendly where geoscientists and drillers can upload MT field data directly from their laptop, tablet or mobile to obtain subsurface geo-electrical distributions quickly with minimal input. This application is designed to be scalable, suiting cloud environments and is currently hosted on an Amazon EC2 instance. The preconceived notion that web applications are slow will be challenged. The purposefully designed MT algorithm and software structure will hopefully result in lower computation times while minimizing restrictions based on hardware requirements (i.e., primary memory).